Neurosurgical indications in the C.B.P. - Gordon-Firing, Sasha; Garbino, Carlos (Cirugía del Uruguay, 1982)
Insidence of brain metastases is evaluated. The dianostic value of T.C. in emphazised. Surical indications and palliative treatment with radiation therapy of intracranial metastases are determined. Spinal chord compression is analysed and the indication of surgery and radiotherapy are discused.